ESENSI DAN PENINGKATAN KOMPETENSI GURU - Mita Fitria; Nurhasanah Sihombing; Rido Gevani; Titi Putri Utami (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2023)
Teachers play a key role in the education and development of young people. The essence of being a teacher is having in-depth knowledge of the subject one teaches, good communication skills, and effective pedagogical skills. Apart from that, a teacher must also have the ability to inspire, motivate and create a safe and inclusive learning environment. Increasing teacher competency is important in ensuring optimal quality of education. Teachers need to continue to develop their knowledge through training, self-development and curriculum updates. Increasing competency also includes the ability to use rapidly developing educational technology. Teachers who continue to learn and adapt can provide a better learning experience for students, face modern-day challenges, and help create a generation that is ready to face the future. In the context of globalization and constant changes in education, the essence of being a quality teacher and continuously improving competence is an important element in achieving the goals of sustainable and inclusive education.